Seco- and isopimarane diterpenoids from Kaempferia marginata rhizomes and their NO inhibition activities. (January 2023) - Do, Kiep Minh; Kodama, Takeshi; Nguyen, Hien Minh; Ikumi, Naoki; Soeda, Chigusa; Shiokawa, Ken-ichi; Morita, Hiroyuki
Abstract: Three undescribed 9, 10-seco-isopimarane diterpenoids, marginols I–K, and an unprecedent isopimara-8(9), 15-diene diterpene, 14- epi -boesenberol F, together with a known 9, 10-seco-isopimarane diterpenoid, kaemgalangol A, were isolated from the rhizomes of Vietnamese Kaempferia marginata . Marginols I and J contained a naturally very rare 6-oxabicyclo[3.2.1]octane-5-ol ring, while marginol K had a naturally rare oxepan-2-one ring in its structure. The unprecedented structures were elucidated by spectroscopic techniques, including HR-ESI-TOF-MS, UV, IR, and 1D and 2D NMR. The absolute configurations of marginols I–K and 14- epi -boesenberol F were determined by ECD calculations. The NO production inhibitory assay revealed that the isolated compounds, except marginol J, exhibited NO inhibitory activities with IC50 values ranging from 65.06 to 87.70 μM against lipopolysaccharide (LPS)-induced RAW264.7 cells. Graphical abstract: Four unreported diterpenoids, together with one known were isolated from the Kaempferia marginata rhizomes. Image 1 Highlights: Five isopimarane diterpenoids were isolated from Vietnamese Kaempferia marginata. Among them, three were undescribed 9, 10-seco-isopimarane diterpenoids. Two unreported contained a naturally very rare 6-oxabicyclo[3.2.1]octane-5-ol ring. One unreported had a naturally rare oxepan-2-one ring. The isolated four compounds showed potent NO production inhibitory activities.